PENGARUH STRATEGI PEMASARAN DAN KUALITAS PELAYANAN TERHADAP PENINGKATAN PENJUALAN DI PT. AYU INDAH GROUP CABANG PACIRAN LAMONGAN - M Hafidh Nasrullah; Muhammad Faizin (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The problem that is known to be related to customer loyality in the PT. Ayu Indah Lamongan is the fluctuation in sales in the past three months. This study aims to influence Strategy marketing and Quality of service on Increased sales in the PT. Ayu Indah Lamongan which is on Jl. Raya Deadles No. 35, Paciran, Lamongan. This research is a survey with quantitative research, population and sample of this study were 60 respondents who bought airplane, car rental etc. in the PT. Ayu Indah Lamongan, data colllection using interviews and questionnaires. Analysis of the data used is the validity test, multiple linear regression analysis, hypothesis testing and the coefficient of determination R2 test.